2021
DOI: 10.15585/mmwr.mm7021e2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Testing to Sustain In-Person Instruction and Extracurricular Activities in High Schools — Utah, November 2020–March 2021

Abstract: On May 21, 2021, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).Cessation of kindergarten through grade 12 in-person instruction and extracurricular activities, which has often occurred during the COVID-19 pandemic, can have negative social, emotional, and educational consequences for children (1,2). Although preventive measures such as masking, physical distancing, hand hygiene, and improved ventilation are commonly used in schools to reduce transmission of SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 9 publications
1
51
0
1
Order By: Relevance
“…Such populations are especially well-suited for sentinel monitoring efforts to detect the early introduction and spread of COVID-19, particularly in areas with low vaccination coverage or where layered prevention strategies are not in use. CDC considers the capacity to monitor COVID-19 incidence in the following populations particularly useful due to their high risk of exposure or severe illness: students and staff members of kindergarten-grade 12 schools and institutions of higher education, health care workers, residents and staff members of long-term care facilities, incarcerated persons, homeless persons, and workers in high-density work sites (18)(19)(20)(21)(22)(23).…”
Section: Capacity For Early Detection Of Increases In Covid-19 Casesmentioning
confidence: 99%
“…Such populations are especially well-suited for sentinel monitoring efforts to detect the early introduction and spread of COVID-19, particularly in areas with low vaccination coverage or where layered prevention strategies are not in use. CDC considers the capacity to monitor COVID-19 incidence in the following populations particularly useful due to their high risk of exposure or severe illness: students and staff members of kindergarten-grade 12 schools and institutions of higher education, health care workers, residents and staff members of long-term care facilities, incarcerated persons, homeless persons, and workers in high-density work sites (18)(19)(20)(21)(22)(23).…”
Section: Capacity For Early Detection Of Increases In Covid-19 Casesmentioning
confidence: 99%
“…Despite the potential burden of regular testing, school-based COVID-19 testing has been found to enhance mitigation efforts, detect asymptomatic cases, limit in-school spread, and maximize in-person learning days. 4,[9][10][11]20 Communicating the value of testing to stakeholders--in both educational and public health terms--is critical to generating buy-in and participation. Finding testing models that are both effective and easy to implement are key to wide scale uptake.…”
Section: Discussionmentioning
confidence: 99%
“…During the 2020-2021 school year, accumulated evidence demonstrated that if mitigation measures are followed, including masking, physical distancing, and vaccinations for those eligible, schools can safely maintain in-person learning while simultaneously not contributing to community spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). [1][2][3][4] COVID-19 symptomatic and screening testing has also been recommended as an additional measure to detect cases and reduce the likelihood of SARS-CoV-2 transmission in schools. 5 Given the significant social support, nutritional assistance, and healthcare benefits afforded by in-person education, keeping schools open and safe from COVID-19 is a significant public health priority for the 2021-2022 school year.…”
Section: Introductionmentioning
confidence: 99%
“…There are substantial logistical and equity concerns that need to be taken into consideration (Table 3). If studied, consideration should be given to using the strategy to promote equity of access to participate in close contact clubs and sports (Test-to-Play strategy) 73 and in situations where screening and/or adherence to public health measures may be more challenging (e.g., students with special needs), without exacerbating inequities based on race, ethnicity or wealth. A COVID-19 Science Advisory Table Science Brief on asymptomatic screen testing for schools is forthcoming.…”
Section: Sars-cov-2 Testing For Schoolsmentioning
confidence: 99%
“…67 In high community risk scenarios, the use of rapid antigen screen testing may be considered in order to maintain function of extra-curricular clubs and athletics, particularly those associated with significant aerosol dispersion indoors, such as choir, wind instruments, football and wrestling ("Test-To-Play" strategy, see Testing section). 73 Of note, rapid antigen screen testing is most effective alongside other mitigation measures, including distancing, masking, efforts to improve air quality, and outdoor activities and play. 125 The following table summarizes recommendations for in-person curricular and extracurricular programs offered through school settings.…”
Section: General Considerationsmentioning
confidence: 99%